Usefulness of Topically Applied Sensors to Assess the Quality of 18F-FDG Injections and Validation Against Dynamic Positron Emission Tomography (PET) Images - Lattanze, Ronald K.; Osman, Medhat M.; Ryan, Kelley A.; Frye, Sarah; Townsend, David W. (Frontiers in Medicine, 2018)
Background: Infiltrations of 18F-fluorodeoxyglucose (FDG) injections affect positron emission tomography/computed tomography (PET/CT) image quality and quantification. A device using scintillation sensors (Lucerno Dynamics, Cary, NC) provides dynamic measurements acquired during FDG uptake to identify and characterize radioactivity near the injection site prior to patient imaging. Our aim was to compare sensor measurements against dynamic PET image acquisition, our proposed reference in assessing injection quality during the uptake period. Methods: Subjects undergoing routine FDG PET/CT imaging were eligible for this Institutional Review Board approved prospective study. After providing informed consent, subjects had sensors topically placed on their arms. FDG was injected into subjects' veins directly on the PET imaging table. Dynamic images of the injection site were acquired during 45 min of the uptake period. These dynamic image acquisitions and subjects' routine standard static images were evaluated by nuclear medicine physicians for abnormal FDG accumulation near the injection site. Sensor measurements were interpreted independently by Lucerno staff. Dynamic image acquisition interpretation results were compared to the sensor measurement interpretations and to static image interpretations. Results: Twenty-four subjects were consented and enrolled. Data from 21 subjects were gathered. During dynamic image acquisition review, physicians interpreted 4 subjects with no FDG accumulation at the injection site, whereas 17 showed evidence of accumulation. In 10 of the 17 cases that showed FDG accumulation, the FDG presence at the injection site resolved completely during uptake corresponding to venous stasis, the temporary sequestration of blood from circulation. Static image interpretation agreed with dynamic images interpretation in 11/21 (52%) subjects. Sensor measurement interpretations agreed with the dynamic images interpretations in 18/21 (86%) subjects. Conclusions: Sensor measurements can be an effective way to identify and characterize infiltrations and venous stasis. Comparable to an infiltration, venous stasis may produce spurious and clinically meaningful measurement bias and possibly even scan misinterpretation. Since the quality and quantification of PET/CT studies are of clinical importance, sensor measurements acquired during the FDG uptake may prove to be a useful quality control measure to reduce infiltration rates and potentially improve patient care. Registration:Clinicaltrials.gov, Identifier: NCT03041090